ANALISIS PEMBERHENTIAN TIDAK DENGAN HORMAT SEBAGAI PEGAWAI NEGERI SIPIL - Azizah, Nida Indriani; Sitabuana, Tundjung Herning (Jurnal Hukum Adigama, 2021)
Civil Servants (PNS) as state apparatus have a central presence in bringing policy components to the realization of national goals and national development. These components are accumulated in the form of distribution of duties, functions and obligations of Civil Servants (PNS). In accordance with the provisions of Article 87 paragraph (4) letter b of the ASN Law, and Article 250 letter b of Government Regulation Number 17 of 2020 concerning PNS Management, Civil Servants (PNS) are dishonorably discharged because "Sentenced to prison or imprisonment based on a court decision has permanent legal force for committing a criminal act of occupational crime or a criminal offense related to office and / or general crimes â€. The problem under study is whether "The decision of PT. TUN Jakarta Number 160/B/2020/PT.TUN.JKT which rejected Gatot Rachmanto's request for the Cirebon Regent's Decree (PLT) Number: 888/Kep/260/BKPSDM dated May 28, 2019 to be postponed while the examination of the State Administration dispute is in progress until a court decision is legally enforceable, it will not contradict the provisions of Article 67 paragraph (2) of the Administrative Court Law. This research was conducted using a normative legal research method, with a statutory approach. The data from this research were processed and analyzed using qualitative analysis techniques, and then presented in narrative form.